If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -7x + 3x = -27 Combine like terms: -7x + 3x = -4x 1 + -4x = -27 Solving 1 + -4x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x = -27 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = -27 + -1 -4x = -27 + -1 Combine like terms: -27 + -1 = -28 -4x = -28 Divide each side by '-4'. x = 7 Simplifying x = 7
| 3b-5z=8 | | 19=3(g+3)+1 | | -1/12x=1/4 | | -38+6x=4(8x-3) | | 4(x-1)-2(3x-2)=3-5(x-3) | | 2(p+2)=16 | | 7/2=21/6 | | 18+5b=3b | | 2(c+14)=37 | | -(8+7p)=-6p-13 | | 11=-5x-5x-9 | | =13-v | | g/2-4g=20 | | (-2/5)x=-4/15 | | h-3/3=4 | | 5(6+5a)=4a-12 | | 7n+12*13n-16*6n=360 | | (7n+12)(13n-16)(6n)=360 | | 3h-10h=-14 | | 2c-2b=-14 | | Ln(x+7)+ln(x)=ln(18) | | -84=-4(3-4n)+2n | | 2(c-14)=37 | | 41=3x+25 | | z-9/-2=-3 | | t-22=14 | | 3r-6=6-r | | 3000/450 | | -.15x=60 | | -26=x/4=9 | | K^2-10k-30=0 | | g+4g-3=12 |